Exposure to Ionizing Radiation Causes Long-Term Increase in Serum Estradiol and Activation of PI3K-Akt Signaling Pathway in Mouse Mammary Gland - Suman, Shubhankar (2012)
PURPOSE: Exposure to ionizing radiation is an established risk factor for breast cancer. Radiation exposure during infancy, childhood, and adolescence confers the highest risk. Although radiation is a proven mammary carcinogen, it remains unclear where it acts in the complex multistage process of breast cancer development. In this study, we investigated the long-term pathophysiologic effects of ionizing radiation at a dose (2 Gy) relevant to fractionated radiotherapy. METHODS AND MATERIALS: Adolescent (6–8 weeks old; n = 10) female C57BL/6J mice were exposed to 2 Gy total body γ-radiation, the mammary glands were surgically removed, and serum and urine samples were collected 2 and 12 months after exposure. Molecular pathways involving estrogen receptor-α (ERα) and phosphatidylinositol-3-OH kinase (PI3K)-Akt signaling were investigated by immunohistochemistry and Western blot. RESULTS: Serum estrogen and urinary levels of the oncogenic estrogen metabolite (16αOHE1) were significantly increased in irradiated animals. Immunostaining for the cellular proliferative marker Ki-67 and cyclin-D1 showed increased nuclear accumulation in sections of mammary glands from irradiated vs. control mice. Marked increase in p85α, a regulatory sub-unit of the PI3K was associated with increase in Akt, phospho-Akt, phospho-BAD, phospho-mTOR, and c-Myc in irradiated samples. Persistent increase in nuclear ERα in mammary tissues 2 and 12 months after radiation exposure was also observed. CONCLUSIONS: Taken together, our data not only support epidemiologic observations associating radiation and breast cancer but also, specify molecular events that could be involved in radiation-induced breast cancer.